Christology in the Digital Age: A Constructive Theological Study - Yoas Tanugraha; Abdon Arnolus Amtiran (PT FORMOSA CENDEKIA GLOBAL, 2026)
The development of digital technology has transformed patterns of human relationships from embodied presence to virtually mediated interactions. This transformation affects not only social communication but also spiritual experiences, church practices, and human understanding of presence. This study aims to construct a theological understanding of the Incarnation in the context of virtual space through a constructive theology approach. The research employs qualitative methods with a systematic Christological approach, contextual theology, and digital theology. Analysis is conducted through conceptual analysis, theological synthesis, and normative-contextual reconstruction of the relationship between the doctrine of the Incarnation and modern digital culture. The results of the study indicate that the deepest core of the Incarnation does not lie solely in physicality, but in the relational presence of a personal and transformative God.